IMPLICATIONS OF THE CONSTITUTIONAL COURT'S DECISION ON THE SEPARATION OF NATIONAL AND LOCAL ELECTIONS FOR INDONESIAN ELECTION LAW POLITICS - Alasman Mpesau; Ruslan (RADJA PUBLIKA, 2026)
Constitutional Court Decision Number 135/PUU-XXII/2024 separates national and local elections with a specific time interval, having implications for the Indonesian electoral system and electoral law policy. This study aims to normatively analyze the impact of this decision on the principle of election simultaneity, transition of terms of office, and future electoral law design. The method used is normative legal research with a legislative approach, case studies, conceptual and comparative studies of the democratic transitions of Germany and South Africa. The results show that Constitutional Court Decision 135 reflects the approach of judicial activism and living constitution, and does not conflict with the 1945 Constitution of the Republic of Indonesia. This separation of elections requires legal reform through harmonization of the Election Law and Regional Elections with an Omnibus Law approach. In addition, it is necessary to refine the electoral system towards a mixed-member proportional model to be more representative and democratic. This decision is an important foundation for reforming electoral law politics that is constitutional, adaptive, and responsive to the dynamics of Indonesian democracy.